Drug susceptibility testing in microaerophilic parasites: Cysteine strongly affects the effectivities of metronidazole and auranofin, a novel and promising antimicrobial. Issue 3 (December 2017) - Leitsch, David
Abstract: The microaerophilic parasites Entamoeba histolytica, Trichomonas vaginalis, and Giardia lamblia annually cause hundreds of millions of human infections which are treated with antiparasitic drugs. Metronidazole is the most often prescribed drug but also other drugs are in use, and novel drugs with improved characteristics are constantly being developed. One of these novel drugs is auranofin, originally an antirheumatic which has been relabelled for the treatment of parasitic infections. Drug effectivity is arguably the most important criterion for its applicability and is commonly assessed in susceptibility assays using in vitro cultures of a given pathogen. However, drug susceptibility assays can be strongly affected by certain compounds in the growth media. In the case of microaerophilic parasites, cysteine which is added in large amounts as an antioxidant is an obvious candidate because it is highly reactive and known to modulate the toxicity of metronidazole in several microaerophilic parasites. In this study, it was attempted to reduce cysteine concentrations as far as possible without affecting parasite viability by performing drug susceptibility assays under strictly anaerobic conditions in an anaerobic cabinet. Indeed, T . vaginalis and E . histolytica could be grown without any cysteine added and the cysteine concentration necessary to maintain G . lamblia could be reduced to 20%. Susceptibilities to metronidazole were found to be clearly reduced in the presence of cysteine. With auranofin the protective effect of cysteine was extreme, providing protection to concentrations up to 100-fold higher as observed in the absence of cysteine. With three other drugs tested, albendazole, furazolidone and nitazoxanide, all in use against G . lamblia, the effect of cysteine was less pronounced. Oxygen was found to have a less marked impact on metronidazole and auranofin than cysteine but bovine bile which is standardly used in growth media for G . lamblia, displayed a marked synergistic effect with metronidazole. Graphical abstract: Image 1 Highlights: T. vaginalis and E. histolytica can grow anaerobically without cysteine. T. vaginalis and G. lamblia are more susceptible to metronidazole without cysteine. T. vaginalis is 100-fold more susceptible to auranofin without cysteine. G. lamblia is 12-fold more susceptible to auranofin with low cysteine. Bovine bile renders G. lamblia more susceptible to metronidazole.